If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -33 = 11x Reorder the terms: -33 + 8x = 11x Solving -33 + 8x = 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. -33 + 8x + -11x = 11x + -11x Combine like terms: 8x + -11x = -3x -33 + -3x = 11x + -11x Combine like terms: 11x + -11x = 0 -33 + -3x = 0 Add '33' to each side of the equation. -33 + 33 + -3x = 0 + 33 Combine like terms: -33 + 33 = 0 0 + -3x = 0 + 33 -3x = 0 + 33 Combine like terms: 0 + 33 = 33 -3x = 33 Divide each side by '-3'. x = -11 Simplifying x = -11
| 2(f-6)=-8 | | l+29=73 | | m-91=4 | | -10(s+5)=-95 | | -1x+13=-5x-7 | | 5=6x-30 | | x*x-2x-4=0 | | 5(t+5)=20 | | 6t=2t-12 | | -22=9+7(k-2) | | 7n-3=60 | | -3(1x+8)=-15 | | -6f-3f=-27 | | f(x)=4x+5(sin^4)x | | b-3.2=1.5 | | -3(1x+8)=15 | | z+4-3=2z | | 123=5x-2(-2x-12) | | 8x-7=2(2+7)-5 | | -v+8=-(v-4) | | 2n+3=n+12 | | -2-5(1-3x)=30 | | 5x^2+12x-39991=0 | | -6(1x+4)=-42 | | (-12)(-6.9)9.5=X(9.5)(-12.3) | | 2m+3m=30 | | -8(1x-1)+8=-2x+64 | | 5m+3-12m=-(7m-14)+6 | | Z-81.6=-18.6 | | -(.66)(-0.3x)(1.5)(-1)= | | -(.625)(5x)(1.6)(12y)(0)= | | 5(1x+6)+13=5x+43 |